Changes in ultrasound imaging of joints, entheses, bursae and tendons 24 and 48 h after adjusted weight training. (July 2022) - Schreiner, Julia K.; Recker, Florian; Scheicht, Dennis; Karakostas, Pantelis; Ziob, Jana; Behning, Charlotte; Preuss, Peter; Brossart, Peter; Schäfer, Valentin S.
Background: Joint effusion and enthesitis are common ultrasound findings in rheumatic diseases such as rheumatoid arthritis or spondyloarthritis. However, changes of joints and entheses were not only observed in patients but also in physically active individuals and athletes. Objectives: The purpose of this study was to evaluate joint, entheseal, bursal and tendon musculoskeletal ultrasound (MSUS) findings in large and medium joints of young healthy individuals after completing a standardised weight training. Design: This is a prospective cohort study. Methods: MSUS examinations of large- and medium-sized joints, and related entheseal sites, bursae and tendons were performed on young healthy individuals (ages 18–30 years). Before, 24 and 48 h after completing 1 h of standardised weight exercise, the subjects were evaluated by MSUS. The development of the MSUS findings and associated effects were examined using generalised linear mixed effects models. Results: In total, 51 healthy individuals (52.9% female) with a mean age of 23.7 (±2.5) years were enrolled. The results showed an increase in the number of individuals with at least one joint effusion from 37 (72.5%) before the weight training to 48 (94.1%) after 48 h. Entheses with pathologies were observed in 14 participants (27.5%) at baseline, increasing to 29 participants (56.9%) 48 h after the weight training. Biceps tendon sheath effusion was detected in 9 individuals (17.6%) prior to training, rising to 22 individuals (43.1%) after 48 h. A significant increase in the number of joints with effusion and abnormal entheses within 48 h after the weight training was indicated by the generalised linear mixed effects models. Conclusion: Within 48 h after the weight training session, a significant increase in the prevalence of joint effusion in large and medium joints and the prevalence of abnormal entheses was observed. As a result, when performing and interpreting an MSUS examination, the patient's physical activities should be taken into account.